A Transformasi Digital UMKM Melalui Pelatihan dan Pendampingan untuk Penguatan Literasi Digital dan Peningkatan Omzet di Kecamatan Lingsar, Lombok Barat - Armiani Armiani; I Made Murjana; Yusi Faizathul Octavia; Topan Siswanto; Nendy Pratama Agusfianto; Khaerul Hadi; Dwi Arini Nursansiwi (Valid Jurnal Pengabdian, 2026)
This Community Service Program (PKM) aims to enhance the capacity of culinary MSME (Micro, Small, and Medium Enterprises) actors in Lingsar District, West Lombok Regency, in utilizing social media as a tool for promotion and sales improvement. Using the Participatory Action Research (PAR) approach, the program was implemented through four main stages: needs analysis, digital marketing training, four-week intensive mentoring, and evaluation and reflection. The mentoring activities focused on three MSMEs representing different culinary sub-sectors, namely traditional dry snacks, catfish floss, and wet cakes. The results showed a significant improvement in participants’ digital literacy, frequency of online promotional content, and an increase in business turnover by 20–30%. The program also fostered collaborative networks among MSME actors to ensure business sustainability through digital platforms. Thus, the PAR approach proved effective in empowering MSMEs toward sustainable digital independence in West Lombok.